Применение комплексов метода конечных элементов для прогнозирования физико-механических характеристик углепластиковых сотовых заполнителей - Сливинский, В.И.; Харченко, М.Е.; Санин, А.Ф.; Липовский, В.И. (Вісник Українського матеріалознавчого товариства, 2013)
Physical and mechanical properties of honeycomb aggregates are seted. Data for cabculation of constructions with carbonlayers using in methods of final results based of natural results.